Comparative outcomes of conservative, steinmann pin, and plate fixation in calcaneal fractures: a subtype-based evaluation according to the essex-lopresti classification - Esmez, Omer; Demir, Sukru; Gurger, Murat; Gulkesen, Arif; Bilek, Furkan (Bmc, 2025)
BackgroundCalcaneal fractures are the most common tarsal fractures and often result in long-term disability. Although various treatment options exist, but the relationship between Essex-Lopresti subtypes, treatment methods, and dynamic functional recovery remains unclear.MethodsThis retrospective study included 66 patients with intra-articular calcaneal fractures, treated between 2011 and 2021. Fractures were categorized according to the Essex-Lopresti classification (1 A-1 C, 2 A-2 C) and managed by conservative treatment, Steinmann pin fixation, or plate fixation. Functional outcomes were assessed, using the American Orthopaedic Foot and Ankle Society (AOFAS) score, radiographic parameters (B & ouml;hler and Gissane angles), and pedographic gait analysis with the Win-Track platform. Statistical analysis was performed using Kruskal-Wallis tests with Dunn-Bonferroni post-hoc analyses, Mann-Whitney U or independent-samples t-tests as appropriate, chi-square (or Fisher's exact) tests for categorical variables, and Spearman's rho for correlation.ResultsFunctional outcomes varied across subtypes and treatment methods. Across subtypes, the distribution of AOFAS categories did not differ significantly (chi(2), p = 0.587). Type 2 A fractures treated with Steinmann pin fixation demonstrated the highest AOFAS scores (80.4 +/- 10.2; p = 0.587). B & ouml;hler's angle was numerically higher in the conservative group (17.0 +/- 11.4 degrees) but did not correlate with AOFAS scores (rho = 0.01, p = 0.94). Pedographic analysis showed that maximum plantar pressure was highest in the conservative group (1625 +/- 142 kPa) and lowest in the plate fixation group (1437 +/- 188 kPa; overall p = 0.033). Gait asymmetries-particularly prolonged swing and stride duration tended to be greater in the Type 2B and 2 C subgroups, although statistical significance was limited ((p = 0.195-0.795)).ConclusionEssex-Lopresti subtypes strongly influence clinical and gait outcomes following calcaneal fractures. Steinmann pin fixation is advantageous in Type 2 A fractures, while Type 2B fractures consistently show poor recovery. Radiographic angles alone are insufficient predictors of long-term outcomes, emphasizing the importance of integrating gait analysis with clinical scoring. Subtype-specific approaches may optimize treatment strategies and patient care.IRB numberEthics Committee of F & imath;rat University (2022/04-04).
Keywords: Calcaneal fracture; Essex-Lopresti classification; Steinmann pin; Plate fixation; Gait analysis